Carbon-Decorated Fe3S4-Fe7Se8 Hetero-Nanowires: Interfacial Engineering for Bifunctional Electrocatalysis Toward Hydrogen and Oxygen Evolution Reactions. Issue 8 (17th April 2020) - Le, Thanh-Tung; Huang, Shoushuang; Ning, Ping; Wang, Wenwen; Wang, Qing; Jiang, Yong; He, Qingquan; Feng, Jialiang; Hu, Zhangjun; Chen, Zhiwen
Abstract : The design and synthesis of complex multi-component heterostructures is an effective strategy to fabricate cost-efficient catalysts for electrochemical water splitting. Herein, one-dimensional porous Fe3 S4 -Fe7 Se8 heterostructured nanowires confined in carbon (Fe3 S4 -Fe7 Se8 @C) were synthesized via the selenization of Fe-based organic-inorganic nanowires. Benefiting from the merits of morphology, composition and surface structure characteristics, i.e., the high structural void porosity, the direct electrical pathways of nanowire topology and the conductive carbon layer coating, the titled catalyst not only offered a larger accessible electrocatalytic interface but also facilitated diffusion of the electrolyte and gas. Moreover, the electron redistribution at the Fe3 S4 -Fe7 Se8 heterojunction interfaces reduced the adsorption free-energy barriers on the active sites, endowing the catalysts with faster reaction kinetics and improved electrocatalytic activity. Accordingly, the optimal Fe3 S4 -Fe7 Se8 @C produced a low hydrogen evolution reaction overpotential of 124 mV at 10 mA cm −2 with a Tafel slope of 111.2 mV dec −1, and an ultralow oxygen evolution reactions overpotential of 219 mV at 20 mA cm −2, respectively. When applied as both anode and cathode for overall water splitting, a low battery voltage of 1.67 V was achieved along with excellent stability for at least 12 h. The work presented here offered a feasible scheme to fabricate non-noble metal-based electrocatalysts for water splitting.